STRATEGI PEMASARAN DALAM MENINGKATKAN HUNIAN KAMAR DI ERA NEW NORMAL PANDEMI COVID-19 PADA THE PAYOGAN VILLA RESORT & SPA KEDEWATAN UBUD GIANYAR - Putu Ade Wijana; Ni Made Hartini; Nuning Kurniawati (Journal of Applied Management Studies, 2022)
The current Covid-19 pandemic which has an impact on declining tourist visits and very high competition in competing for tourists, the management of The Payogan Villa Resort & Spa must be able to implement the right strategy in the midst of the Covid-19 pandemic to maintain the continuity of the company. The research method used is SWOT analysis, which analyzes strength, weakness, opportunities, and threats as a strategy formula for developing marketing strategies. Determination of research samples using Purposive Sampling technique. The strength of The Payogan Resort & Spa Ubud Gianyar is that it has a strategic location, competitive room prices, complete room facilities, friendly staff, attractive restaurant menu, ease of transportation, excellent facilities. The downsides are that promotion has not been maximized, service is not fast enough, the appearance of employees is less attractive. The opportunity is the optimism of tourists traveling to travel, the attitude of the community is still high and there is support from the government. The threat is competition, government policy towards foreign tourist permits, tourist bargaining power. Marketing strategies in increasing room occupancy in the New Normal Era of the Covid-19 Pandemic at The Payogan Resort & Spa Ubud Gianyar with pricing strategies, digital marketing promotion strategies, strategies for increasing cooperation with trevel agents and other companies, strategies for developing tour packages and strategies for improving product quality and human resources